Girls On Key. How female spoken-word poetry is driving the participation of women in literature - Rejane Pivetta de Oliveira; Tatiana Borges da Cruz (Funes)
This article examines the spoken-word poetry movement carried out by women in saraus (soirées) and slams, focusing, more specifically, on the Sarau Nosotras, which occurs in the Porto Alegre literary scene. The interest is in observing the event as a space of poetic performance (ZUMTHOR, 2001) closed to male participation, based on a critical perspective that contemplates the identitarian turn triggered by the feminist explosion (HOLLANDA, 2018) and the emergence of representations of peripheral subjects (SPIVAK, 2010; KILOMBA, 2019). In this context, the aim is to demonstrate that the intense participation of women in the spoken-word poetry scene, which is amplified by the digital universe (CASTELLS, 2013), places new agencies on the agenda, giving visibility to a production that challenges the canonical tradition of literature as a production of narrative and memory.